Answer: P(3) is True
Step-by-step explanation:
The given statement is an inequality denoted as P(x). To find out which of the options is true you have to evaluate each given value of X in the inequality and perform the arithmetic operations, then you have to see if the expression makes sense.
For P(0): Replace X=0 in 2x+5>10
2(0)+5>10
0+5>10
5>10 is false because 5 is not greater than 10
For P(3): Replace X=3 in 2x+5>10
2(3)+5>10
6+5>10
11>10 is true because 11 is greater than 10
For P(2): Replace X=2 in 2x+5>10
2(2)+5>10
4+5>10
9>10 is false
For P(1): Replace X=1 in 2x+5>10
2(1)+5>10
2+5>10
7>10 is false
w represents width
4w represents length
d represents diagonal
w2 + (4w)2 = d2
w2 + 16w2 = d2
17w2 = d2
±w√17 = d
The diagonal is the width times √17.
These are the two rules for when a and b are positive numbers.
a + b = b + a
a - b ≠ b -a
a - b = -b + a
For example:
5.71 + 2.84 = 2.84 + 5.71
8.55 = 8.55
5.71 - 2.84 ≠ 2.84 - 5.71
2.87 ≠ -2.87
5.71 - 2.84 = -2.84 + 5.71
2.87 = 2.87
These are the rules for when a and b are negative numbers.
a + b = b + a
a - b = b + a
For example,
-6.2 + (-3.96) = -3.96 + (-6.2)
-6.2 - 3.96 = -3.96 - 6.2
-10.16 = -10.16
-6.2 - (3.96) = -3.96 + (-6.2)
-10.16 = -10.16
Also, if a is a positive number, while b is a negative number, we see these rules:
a + b = a - b
a - b = a + b
For example,
5.71 + (-6.2) = 5.71 - 6.2
-0.49 = -0.49
5.71 - (-6.2) = 5.71 + 6.2
11.91 = 11.91
Also, if a is a negative number while b is a positive number, then these rules will apply:
a + b = b - a
a - b = -b - a
For example,
-3.96 + 2.84 = 2.84 - 3.96
-1.12 = <span>-1.12
</span>
-3.96 - 2.84 = -2.84 - 3.96
-6.8 = -6.8
I hope this helps! :)
Our answer is

Our greatest common factor, or GCF, is

, so when we factor is out, our divide each term by

, we get our answer. To check this, we can multiply the

back across the parenthesis and see if we get the same result as our initial question.
Hope this helped! :))